Environmental campaign in the documentary film Ekspedisi 3 Sungai episode Juara Sampah Saset - Hanief, Lalita; Ainani, Muhammad; Nurfatmawati, Atik (Universitas Padjadjaran, 2026)
Background: This research analyzes the function of environmental communication in the documentary film